Representasi Gaya Hidup Studi di Luar Negeri Dalam Unggahan Instagram Influencer Gitasav (Universitas Negeri Surabaya, 2021)
Instagram allows users to share photos and videos on their daily activities through their lifestyle. Users that have the freedom to share photos and videos, lead those creative individuals to make the content enticing and invite other users to be interested in visiting their page. From here comes the term of celebgram or influencer, they have thousands and even millions of followers and makes an individual with their uniqueness as a role model to be followed in their daily activities. The researcher is interested in describing how the educational lifestyle is displayed in posts on Instagram as a social media, taking the research titled as